ANTIMICROBIAL RESISTANCE AND OPTIMIZATION OF ANTIMICROBIAL THERAPY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Antimicrobial resistance represents one of the most formidable challenges to contemporary healthcare systems worldwide. This investigation examines the molecular mechanisms underlying resistance development, identifies critical gaps in current prescribing practices, and evaluates evidence-based strategies for optimizing antimicrobial therapy. Through analysis of international surveillance data, clinical guidelines, and pharmacodynamic principles, this study demonstrates that structured antimicrobial stewardship programs combined with precision-guided therapy can substantially mitigate resistance propagation. The findings underscore the urgent need for integrated approaches encompassing diagnostic innovation, prescriber education, and policy reform to preserve antimicrobial efficacy for future generations.